Reforming pedagogical education in Germany in the context of socio-political changes (Pedagogy of Higher and Secondary Education, 2021)
The article deals with the questions of pedagogical educations reform in Germany on the contemporary level of teachers' preparation under the social-political and economic conditions (the end of 21th centuries).
Keywords: system of teachers' education; contents of pedagogical education; foreign languages education; intercultural teaching